2016
DOI: 10.1039/c6nr06504j
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the interaction between a semiconductor nanosphere and a thin metal film for nanoscale plasmonic devices

Abstract: The interaction of silicon (Si) nanospheres (NSs) with a thin metal film is investigated numerically and experimentally by characterizing their forward scattering properties. A sharp resonant mode and a zero-scattering dip are found to be introduced in the forward scattering spectrum of a Si NS by putting it on a 50-nm-thick gold film. It is revealed that the sharp resonant mode arises from a new magnetic dipole induced by the electric dipole and its mirror image while the zero-scattering dip originates from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 41 publications
(65 reference statements)
2
33
0
Order By: Relevance
“…It is noticed that the MD moment contributes negatively to the total extinction in the presence of the Ag film, because of bianisotropic effect implying a destructive interference between the fields scattered by the ED and MD moments [36]. More importantly, such bianisotropic effect also results in the shrinkage of the ED resonance's line width [14], as clearly shown in Figure 1C.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…It is noticed that the MD moment contributes negatively to the total extinction in the presence of the Ag film, because of bianisotropic effect implying a destructive interference between the fields scattered by the ED and MD moments [36]. More importantly, such bianisotropic effect also results in the shrinkage of the ED resonance's line width [14], as clearly shown in Figure 1C.…”
Section: Resultsmentioning
confidence: 86%
“…Similarly, the hybrid concept was used to boost the Purcell factor and generate efficient hot electron luminescence from a silicon (Si) nanowire coated with a thin Ag film [12]. Furthermore, such a strategy can be generalized to the three-dimensional case for realizing strong localization of optical field in particleon-film systems where dielectric nanoparticles (such as Si nanospheres) supporting distinct Mie resonances were used [13,14]. As an exemplary application, the significantly enhanced electric field mediated by the mirrorimage-induced magnetic dipole mode was exploited to enhance Raman scattering and photoluminescence [15].…”
Section: Introductionmentioning
confidence: 99%
“…As some examples, we will show in the following numerical simulation the possible applications of the sharp MD resonance in nanoscale sensing and color display. For practical applications, the metal substrate is chosen to be a 50- nm-thick Au film, which has been used in our previous study [28]. The physical mechanism for the line width compression of the magnetic dipole resonance is the coherent interaction of the magnetic dipole and its mirror image induced by the metal substrate.…”
Section: Practical Applicationsmentioning
confidence: 99%
“…Previously, it has been demonstrated that intensity shift sensors based on Si NS dimers possess much higher sensitivity than wavelength shift sensors based on plasmonic nanoparticles/nanostructures [51]. In addition, the sensitivity of the Si NS placed on a metal substrate and excited by linearly polarized light was also experimentally studied in our previous work [28]. In our case, the scattering spectrum dominated by a sharp MD resonance with a narrow line width is quite suitable for sensing applications, as demonstrated in the following.…”
Section: Practical Applicationsmentioning
confidence: 99%
“…In principle, the scattering properties of the Si NS can be modified by varying either the surrounding environment or the illumination configuration . It has been shown that both the forward and backward scattering spectra of a Si NS can be changed by using a metal film . Moreover, it has been demonstrated that optical pulling force acting on a nanoparticle can be generated by using a single Bessel beam or two interfering plane waves which modify the forward and backward scattering properties of the nanoparticle .…”
Section: Introductionmentioning
confidence: 99%